The evolution and role of continuous medical education (CME) - Macelloni, Barbara (Henry Stewart Talks, 2009)
CME evolution and current status: a focus on Europe, Medical education: role through the brand life cycle and added value of CME, Planning the integration: how to develop effective medical education consistent with the communication strategy, Marketing and medical education departments working together: how to make it a win-win cooperation